1995
DOI: 10.1007/bf01718424
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and sequence determination of the peplomer protein gene of feline infectious peritonitis virus type I

Abstract: cDNA clones spanning the entire region of the peplomer (S) gene of feline infectious peritonitis virus (FIPV) type I strain KU-2 were obtained and their complete nucleotide sequences were determined. A long open reading frame (ORF) encoding 1464 amino acid residues was found in the gene, which was 12 residues longer than the ORF of the FIPV type II strain 79-1146. The sequences of FIPV type I and mainly -tPV type II were compared. The homologies at the N- (amino acid residues 1-693) and C- (residues 694-1464) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
62
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 30 publications
0
62
0
Order By: Relevance
“…FCoVs are classified into types I and II according to their S protein properties (Hohdatsu et al, 1991a;Motokawa et al, 1995Motokawa et al, , 1996. FCoVs are also classified into two biotypes based on differences in pathogenicity: feline enteric coronavirus (FECV) and FIPV.…”
Section: Feline Infectious Peritonitis Virus (Fipv) Is Classified As mentioning
confidence: 99%
See 1 more Smart Citation
“…FCoVs are classified into types I and II according to their S protein properties (Hohdatsu et al, 1991a;Motokawa et al, 1995Motokawa et al, , 1996. FCoVs are also classified into two biotypes based on differences in pathogenicity: feline enteric coronavirus (FECV) and FIPV.…”
Section: Feline Infectious Peritonitis Virus (Fipv) Is Classified As mentioning
confidence: 99%
“…FCoVs have a single-stranded, positive-sense, linear RNA genome and are mainly composed of nucleocapsid (N), transmembrane and spike (S) proteins (Olsen, 1993). FCoVs are classified into types I and II according to their S protein properties (Hohdatsu et al, 1991a;Motokawa et al, 1995Motokawa et al, , 1996. FCoVs are also classified into two biotypes based on differences in pathogenicity: feline enteric coronavirus (FECV) and FIPV.…”
mentioning
confidence: 99%
“…The results support the previous findings that mouse MAbs which show high ADE activities have neutralizing activities, suggesting a close relationship between the neutralization and enhancement sites. We have recently reported that type I FIPVs including the UCD-1 strain have spike genes that are distinctly different from those of type II FIPVs, TGEV and CCV [18,19]. It has been reported that neutralization/enhancement site of the type II FIPV 79-1146 strain is located at the site corresponding to neutralization site A identified on TGEV S protein [3,20].…”
Section: Ade Of Fipv Strain 79-1146 Infection In Human Monocyte Cell mentioning
confidence: 99%
“…Recently, these findings were confirmed by sequence analysis. The sequences of spike genes of type II FCoVs have higher homologies with those of TGEV and CCV than those of type I isolates [18,19]. Dengue virus which causes DHF/DSS has four serotypes differentiated by the neutralization test, and ADE of dengue virus infection often occurs in re-infection with a different serotype of the virus [6,8,9,16,17].…”
mentioning
confidence: 99%
“…In other words, one could identify an isolate as FIPV or FECV, regardless of clinical conditions of the cat from which it was isolated, only after experimental determination of its disease-causing potential in cats. FECV is epizootiologically the predominant FCoV in the field, and it has been tentatively concluded that FIPV is a mutant of FECV, though the exact mutation mechanism has yet to be clarified [4,21,23,29].FCoVs are divided into two distinct serotypes I and II by neutralization specificities induced by a spike protein [5,10,11,19]. Serotype I FCoV isolates have been numerically superior [22] and predominantly distributed among cats [9].…”
mentioning
confidence: 99%